The Sigma-1 Receptor: When Adaptive Regulation of Cell Electrical Activity Contributes to Stimulant Addiction and Cancer - Soriani, Olivier; Kourrich, Saïd (Frontiers in Neuroscience, 2019)
The sigma-1 receptor (σ1R) is an endoplasmic reticulum (ER)-resident chaperone protein that acts like an inter-organelle signaling modulator. Among its several functions such as ER lipid metabolisms/transports and indirect regulation of genes transcription, one of its most intriguing feature is the ability to regulate the function and trafficking of a variety of functional proteins. To date, and directly relevant to the present review, σ1R has been found to regulate both voltage-gated ion channels (VGICs) belonging to distinct superfamilies (i.e., sodium, Na+; potassium, K+; and calcium, Ca2+ channels) and non-voltage-gated ion channels. This regulatory function endows σ1R with a powerful capability to fine tune cells’ electrical activity and calcium homeostasis—a regulatory power that appears to favor cell survival in pathological contexts such as stroke or neurodegenerative diseases. In this review, we present the current state of knowledge on σ1R’s role in the regulation of cellular electrical activity, and how this seemingly adaptive function can shift cell homeostasis and contribute to the development of very distinct chronic pathologies such as psychostimulant abuse and tumor cell growth in cancers.